Transformasi Komunikasi Pemasaran di Era Artificial Intelligence - Aulia, Dinni (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
The limitations of traditional advertising formats and the advent of the internet have driven a shift in the advertising industry toward the digital era, making modern advertising more effective and efficient. This transformation has also reshaped the landscape of marketing communication. Innovations in artificial intelligence (AI) play a critical role in facilitating marketing communication in the digital age, enabling companies to engage audiences in more personal and compelling ways. This study aims to explore the role of AI in enhancing the effectiveness of marketing communication compared to traditional methods. It employs a systematic literature review methodology guided by PRISMA protocols. The research focuses on analyzing academic literature and previous empirical studies on AI's role in content personalization, marketing efficiency, consumer behavior analysis, and its impact on customer engagement. The findings reveal that AI offers significant advantages over traditional methods, including improved content personalization, enhanced marketing efficiency, better consumer insights, increased customer engagement, and cost savings. However, challenges such as limited consumer understanding of AI and concerns over data privacy underscore the need for a more humanistic and transparent approach, emphasizing clear communication of AI's tangible benefits to consumers. Successful AI integration requires balancing human expertise with machine capabilities, aligning with broader business strategies, and addressing ethical considerations in its application.